study Desain & Implementasi BUSINESS INTELLIGENCE pada suatu maskapai penerbangan (laporan penelitian magang MSIB) - Guruh Sukmo; Sulung Rahmawan Wira Ghani (Teknik Industri, Fakultas Teknik, Universitas Hasyim Asy'ari, 2023)
Satisfying service is a priority for airlines so airlines compete to create comfort. In addition, flights also affect external matters because the airline needs to minimize errors which often occur. To overcome this, it is necessary to monitor the performance of airlines. One method used is the application of a business intelligence system which can provide reporting dashboards that can provide interactive data analysis information. The amount of data from flight traffic stored in the data warehouse becomes very useful if managed properly to get various kinds of hidden insights. With the implementation of business intelligence, the data can be utilized so it becomes a tool in making decisions for the development and improvement of air traffic and the impact of air traffic. The object of this research used raw data from public data. This research method used the Business Intelligence Roadmap (BIR). The results of the study made 3 dashboards: the first dashboard showed a pattern which was almost the same as the total delay data in 3 consecutive years. This was due to a high proportion of weather conditions in America. The second dashboard depicted a positive correlation between airplane visits and economic growth. The third dashboard indicated the number of flights that were frequently used by passengers as a standard reference that the need for and comfort for aircraft facilities because the quality of service provided by the airline was very important for consumers who used flight services.